2019
DOI: 10.1016/j.radonc.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Nodal failure after chemo-radiation and MRI guided brachytherapy in cervical cancer: Patterns of failure in the EMBRACE study cohort

Abstract: To investigate the patterns of nodal failure in patients enrolled in the international multicentre EMBRACE study. Materials/Methods: Nodal disease at diagnosis (NÀ, N+) and nodal failure were analysed per region (NF) (pelvic (parametrial, common iliac, internal/external iliac), inguinal and para-aortic (PAO)) in 1338 patients. Treatment consisted of chemo-radiation and MRI guided brachytherapy. PAO radiotherapy and/or nodal boost was left to the treating centre. At time of diagnosis 52% of patients had patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 28 publications
1
51
1
Order By: Relevance
“…We found that prophylactic para aortic RT reduced the incidence of para aortic lymph node failures as well as distant metastasis when compared to pelvic RT alone. In the Embrace cohort, Nomden et al analyzed pelvic lymph node status at diagnosis and the patterns of failures [5] . It was seen that almost half of the cohort had pelvic lymph node involvement at diagnosis and elective radiation to para aortic region in these patients reduced failure rate to 7% in patients with documented pelvic lymph nodes [5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that prophylactic para aortic RT reduced the incidence of para aortic lymph node failures as well as distant metastasis when compared to pelvic RT alone. In the Embrace cohort, Nomden et al analyzed pelvic lymph node status at diagnosis and the patterns of failures [5] . It was seen that almost half of the cohort had pelvic lymph node involvement at diagnosis and elective radiation to para aortic region in these patients reduced failure rate to 7% in patients with documented pelvic lymph nodes [5] .…”
Section: Discussionmentioning
confidence: 99%
“…In the Embrace cohort, Nomden et al analyzed pelvic lymph node status at diagnosis and the patterns of failures [5] . It was seen that almost half of the cohort had pelvic lymph node involvement at diagnosis and elective radiation to para aortic region in these patients reduced failure rate to 7% in patients with documented pelvic lymph nodes [5] . A Cochrane review of studies which tested EF-RT showed improved para aortic region and distant control when compared to pelvic RT alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, within the same patient, tumour biology of within separate lymph nodes may be similar. During median follow-up of 15 months, lymph node relapse rate was 15% (literature 11–13%), and overall failure was 20% (literature 20%) [5] , [32] , [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…However, LNs failure are more often in PALN region. Of patients with nodal failure, 39% were located in PALN region ( 10 ). Huang et al ( 11 ) reported that 11% of patients with cervical cancer experienced PALN recurrence after pelvic radiotherapy.…”
Section: Introductionmentioning
confidence: 99%